2021
DOI: 10.1101/2021.06.15.448419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphatidylserine Receptors Enhance SARS-CoV-2 Infection: AXL as a Therapeutic Target for COVID-19

Abstract: Phosphatidylserine (PS) receptors are PS binding proteins that mediate uptake of apoptotic bodies. Many enveloped viruses utilize this PS/PS receptor mechanism to adhere to and internalize into the endosomal compartment of cells and this is termed apoptotic mimicry. For viruses that have a mechanism(s) of endosomal escape, apoptotic mimicry is a productive route of virus entry. We evaluated if PS receptors serve as cell surface receptors for SARS-CoV-2 and found that the PS receptors, AXL, TIM-1 and TIM-4, fac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 59 publications
0
22
1
Order By: Relevance
“…These data are in contrast to the conclusions of another report, which points out that AXL does not interact with SARS-CoV-2 spike proteins, and neither does it mediate SARS-CoV-2 entry unilaterally, however, it is a host factor promoting SARS-CoV-2 entry (39). Under synergistic effects of low-level ACE2, AXL interacted with viral particle-related phosphatidylserine (PS) to enhance SARS-CoV-2 infection, while the effects of AXL were no longer observed at high ACE2 levels (39). Since expression levels of ACE2 in the lungs are low, AXL may be highly correlated with SARS-CoV-2 infections.…”
Section: Receptor: Axlcontrasting
confidence: 99%
“…These data are in contrast to the conclusions of another report, which points out that AXL does not interact with SARS-CoV-2 spike proteins, and neither does it mediate SARS-CoV-2 entry unilaterally, however, it is a host factor promoting SARS-CoV-2 entry (39). Under synergistic effects of low-level ACE2, AXL interacted with viral particle-related phosphatidylserine (PS) to enhance SARS-CoV-2 infection, while the effects of AXL were no longer observed at high ACE2 levels (39). Since expression levels of ACE2 in the lungs are low, AXL may be highly correlated with SARS-CoV-2 infections.…”
Section: Receptor: Axlcontrasting
confidence: 99%
“…Research showed that the binding affinity of SARS-CoV-2 to ACE2 was similar to or even higher than the binding affinity of SARS-CoV to ACE2, consistent with the high structural similarity between SARS-CoV-2 and SARS-CoV [83][84][85][86]. Additionally, neuropilin-1 (NRP-1) and the tyrosine-protein kinase receptor UFO (AXL) were identified as receptors to facilitate SARS-CoV-2 infection of the human respiratory system [87][88][89][90]. The overall structural homology and high affinity to the same receptor of these two viruses may explain the high transmission rates of SARS and COVID-19 from human to human [84,85].…”
Section: The Structure and Pathogenesis Of Sars-cov-2mentioning
confidence: 73%
“…Phosphatidylserine (PS) is expressed in the outer leaflet of the viral envelope, with a symmetrical location rather than the asymmetrical phospholipid distribution observed in the normal plasma membrane [5]. As with all enveloped viruses, this facilitates cell entry of SARS-CoV-2 using the apoptotic mimicry pathway [6]. PS receptors (PSRs), Axl in particular, was shown to potentiate the binding and uptake of SARS-CoV-2 [6].…”
Section: Sars-cov-2 Infection and Efferocytosismentioning
confidence: 99%
“…As with all enveloped viruses, this facilitates cell entry of SARS-CoV-2 using the apoptotic mimicry pathway [6]. PS receptors (PSRs), Axl in particular, was shown to potentiate the binding and uptake of SARS-CoV-2 [6].…”
Section: Sars-cov-2 Infection and Efferocytosismentioning
confidence: 99%
See 1 more Smart Citation